Pengaruh Lifestyle, Islamic Branding Dan E-Service Quality Terhadap Keputusan Pembelian Online Produk Fashion Muslim Melalui Media Sosial Instagram (Studi Pada Masyarakat Muslim Provinsi Jawa Barat) - Cupian Cupian; Luthfiah Khairunisa; Sarah Annisa Noven (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this research is to analyze the influence of lifestyle, Islamic branding and e-service quality on purchasing decisions of online products fashion Muslim through social media Instagram on Muslim residents of West Java province. There are several variables used, namely lifestyle, Islamic branding and e-service quality. This research uses a quantitative research type. The information used in this research uses primary data and secondary data. Primary data was obtained from questionnaire information online that was collected and filled out by respondents, on the other hand, secondary information in this research was obtained through literature research from several dailies, the Ministry of Industry and the Ministry of Religion. The Muslim community of West Java Province who recognize products fashion Muslim and who are interested in buying productsÂ fashion Muslimas many as 384 respondents were used as respondents in this research. Collecting information using non-probability sampling method withÂ purposive sampling method. This research uses a descriptive quantitative approach. Information analysis used binary logistic regression analysis. The results of the research show that Lifestyle, Islamic branding, E-service Quality have a positive and significant influence on Purchase Decisions for Online Products Fashion Muslim through Instagram Social Media.Â